2018
DOI: 10.1080/15388220.2017.1423492
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between peer victimization, cognitive appraisals, and adjustment: A systematic review

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 75 publications
4
26
0
1
Order By: Relevance
“…As adolescents move toward greater independence, this may be reflected in a greater importance placed on other adults in their social network (e.g., teachers) and friends (Bokhorst et al, 2010;Helsen, Vollebergh & Meuus, 2000). Therefore, the different findings reported in these studies may reflect developmental differences in the importance of different forms of perceived support (Pössel et al, 2018;Noret et al, 2018). Despite the inconsistent findings, those studies reporting a buffering role for parent and/or teacher support found it to be protective, where the relationship between experiences of being bullied and mental health difficulties was weaker for those with greater perceived support in these domains.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…As adolescents move toward greater independence, this may be reflected in a greater importance placed on other adults in their social network (e.g., teachers) and friends (Bokhorst et al, 2010;Helsen, Vollebergh & Meuus, 2000). Therefore, the different findings reported in these studies may reflect developmental differences in the importance of different forms of perceived support (Pössel et al, 2018;Noret et al, 2018). Despite the inconsistent findings, those studies reporting a buffering role for parent and/or teacher support found it to be protective, where the relationship between experiences of being bullied and mental health difficulties was weaker for those with greater perceived support in these domains.…”
Section: Introductionmentioning
confidence: 81%
“…In a bullying context, support from friends and peers is the most frequently studied form of domain-specific perceived support. Findings from these studies have also yielded inconsistent findings (Noret et al, 2018). Some studies have demonstrated a protective buffering role in boys but not girls (Cheng et al, 2008;Tanigawa et al, 2011), and some studies have demonstrated this finding in girls but not in boys (Lim et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations